Die houding van skoolverlaters teenoor verpleging - M. Beukes (AOSIS, 1982)
While there is an ever-increasing demand for nurses, fewer young women are prepared to enter the nursing profession. Research was undertaken to determine the attitude of White female school leavers towards nursing. Findings indicated that schoolleavers were ignorant about nursing and that more attention should be given to correct career guidance and the recruitment value of the qualified nurse as a role model. Salaries were found to be a major deterrent and the recently improved salary scales should have a marked influence on the attitude of the community towards nursing.